Emerging muscarinic receptor antagonists for the treatment of asthma. (2nd April 2020) - Matera, Maria Gabriella; Belardo, Carmela; Rinaldi, Michele; Rinaldi, Barbara; Cazzola, Mario
ABSTRACT: Introduction: The increased acetylcholine signaling in asthma pathophysiology offers the rationale for the use of LAMAs in the treatment of asthmatic patients. Tiotropium is still the only LAMA approved for use in asthma but there is a real interest in developing novel LAMAs for the treatment of asthma, or at least to extend this indication to other LAMAs already on the market. Areas covered: We examined and discussed trials and research that have studied or are evaluating the role of LAMAs already on the market in asthma and possible novel muscarinic acetylcholine receptor antagonists. Expert opinion: Glycopyrronium and umeclidinium will soon be included in the GINA strategy with the same current indications of tiotropium. It is likely that the choice of the LAMA will be influenced not so much by its pharmacological profile as by the type of triple therapy chosen. It is extremely difficult to identify a new LAMA that is more effective than tiotropium, but is it plausible that new technologies that will allow delivering the drug in a more targeted way and with a lower risk of adverse effects may represent the real progress in the use of LAMAs in asthma in the coming years.